A high‐throughput screening method for the discovery of Saccharomyces and non‐Saccharomyces yeasts with potential in the brewing industry. Issue 3 (30th August 2021) - Aguiar‐Cervera, Jose E.; Delneri, Daniela; Severn, Oliver
Abstract: Both Saccharomyces and non‐ Saccharomyces yeast strains are of great importance for the fermentation industry, especially with the flourishing of craft breweries, which are driving current innovations. Non‐conventional yeasts can produce novel beverages with attractive characteristics such as flavour, texture, and reduced alcohol content; however, they have been poorly explored. A new method for screening the fitness of conventional and non‐conventional yeast libraries utilising robotic platforms and solidified media representing industrial conditions is proposed. As proof of concept, a library formed of 6 conventional and 17 non‐conventional yeast strains was distributed in 96, 384 and 1536 arrays onto a YPD agar medium. Following this, the library was replicated in different conditions mimicking beer and cider fermentation conditions. The colony size was monitored over time, and fitness values measured in maximum pixels/h and maximum biomass were calculated. Significant differences in growth were observed in between the different strains and conditions. As examples, Candida milleri Y‐7245 displayed good performance in wort conditions, and Kazachstania yakushimaensis Y‐48837 stood out for its performance in apple juice. The method is proposed to be used as a pre‐screening step when studying vast yeast libraries. This would enable interested parties to discover potential hits for further study at a low initial cost. Furthermore, this method can be used in other applications where the desired screening media can be solidified.